Video as a Media of Sexual Education for Adolescence - Kartika Adyani; Friska Realita; Ariska Afrianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Problems that often arise in adolescents are sexuality, such as premarital sexual behavior. One of the causes of premarital sex is the lack of knowledge of adolescents about sex education. This knowledge is one of the factors that determine the attitude of adolescents in responding to the information received. This study aims to create video media to provide sexual health education to adolescents. This type of research is Research and Development (R&D) using the ADDIE model. The subjects in this study were five junior high school adolescents aged 11-14 years and one media expert, two material experts, and one language expert. Data were collected through interview guideline instruments and questionnaire sheets—data analysis of the validation questionnaire sheet and student response assessment with quantitative and qualitative analysis. The results of the research developing sexual education videos for adolescents are very good or feasible to be tested because based on the results of the validity test by media experts getting a score of 4.7, tarbiyah jinisiyah material experts with a score of 4.77, reproductive health material experts with a score of 4.58, linguists with a score of 4.3, and student response assessment with a score of 4.65. Thus, the sexual education video media for adolescents is in the very good category or declared feasible to be tested. The implications of this research are expected to reduce violence and sexual crimes in children because children can apply sex education, especially to protect themselves.